Konsep Kafa’ah Dalam Pernikahan Menurut Hukum Islam - Nursaniah Harahap; Faisar Ananda Arfa (Peneliti.net, 2023)
Marriage will achieve peace, tranquility, happiness and serenity both physically and mentally, known as sakinah, mawaddah warohmah, it needs to be well planned and mature. The thing that must be planned is someone who is chosen to be used as a life partner, that person must meet the criteria set both in Islam and other rules. The purpose of this study is to reveal the concept of sekufu in determining companions according to Islamic teachings. This type of research is library research, namely research that focuses on literature by analyzing the content of some related literature. Results of the discussion Choosing a mate is part of the sunnah recommended by the Prophet Muhammad, he said